CO-RELATION OF HISTOPATHOLOGICAL DIAGNOSIS WITH CONVENTIONAL RMI SCORING IN EVALUATION AND DIFFERENTIATION OF BENIGN FROM MALIGNANT ADNEXAL MASS - Dr Sachin Siddu; Dr Sadhana Bharati; Dr Anita Gond; Dr Sunil Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: To study the efficacy and reliability of RMI scoring in differentiating malignant from benign adnexal mass and its co-relation with histopathological diagnosis. METHODS: This is hospital based observational study for a period of 1 year which included 133 patients of adnexal mass attending the OPD who required admission and operative intervention. All cases underwent clinical examination, ultrasonography and RMI scoring. Following surgery specimens were sent for histopathological examination and the reports were co-related with RMI scoring. RESULTS: Out of the total of 133 patients, 33(24.8) patients had malignant adnexal mass, and 100(75.2%) patients had benign adnexal mass. The average RMI for benign and malignant mass was 66.89 and 1341.88 respectively and p value is <0. 001. Out of 33 malignant tumors, 5(15.15%) had RMI <200 and among 100 benign tumors, 95 had RMI<200. Out of 33 malignant tumors, only 28 (84.84) had RMI score >200 where out of 100 benign tumors only ,5 (5%) had RMI score >200. The sensitivity, specificity, positive and negative predictive value of RMI cut off score are 84%, 95%, 95% and 84%. The mean RMI in benign cases is 48.57 (±82.11), while in malignant cases, it is significantly higher at 999.75 (±2082.83). The t-value is -4.32 with a p-value of less than 0.001, indicating a highly significant difference. The benign group contained 8 (8.99%) persons with a menopause score of 0, whereas the malignant group had none. The benign group comprised 54 persons (60.67%) with a menopause score of 1, whereas the malignant group had 16 (37.21%). In the benign group, 27 (30.34%) had a score of 3, whereas 27 (62.79%) in the malignant group. CONCLUSION: The present study demonstrated that RMI scoring is a reliable, effective and simple method in determining the risk of malignancy in adnexal mass in low resource settings. It can be used as a primary method in differentiating malignant adnexal mass from benign, can also be used as an index of referral to higher center from an institute with limited resources for further evaluation and management.